UNIVERSITY 3.0: METHODICAL APPROACHES TO THE SCIENTIFIC AND INNOVATIVE DEVELOPMENT MANAGEMENT - Yu. G. Alekseev; N. A. Dudko (Цифровая трансформация, 2018)
The article is dedicated to the issues of effective universities transformation into centers of advanced science and innovative entrepreneurship within the framework of the concept «University 3.0». There is grounded the necessity of a management systems formation of universities scientific and innovative development, which allow revealing resources and methods for an effective scientific and innovative potential reproduction. The article was prepared within the framework of scientific research aimed at the scientific and technical support of the Ministry of Education activity: «Improving the management model of scientific and innovative development of subordinate to the Ministry of Education of the Republic of Belarus higher education institutions and scientific organizations» (State Registration No. 20170270).